2006
DOI: 10.1007/s10661-006-9547-4
|View full text |Cite
|
Sign up to set email alerts
|

Butyltin Compounds in Sediments of the Bahía Blanca Estuary, Argentina

Abstract: Systematic measurements of both Tributyltin (TBT) and Dibutyltin (DBT) in sediments along different locations in the inner zone of Bahía Blanca estuary were done. Two samples were taken near the main dry dock facility, at Puerto Belgrano naval base, in Argentina. TBT concentrations from non-detected to 170.3 ng Sn g(-1) were measured in the inner region of the estuary, and higher one of 3,288 ng Sn g(-1) near the dry dock at Puerto Belgrano. DBT values ranging between non-detected and 75.2 ng Sn g(-1) were obt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
2
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 13 publications
0
15
2
1
Order By: Relevance
“…Sediment TBT concentrations near a shipyard in Otuschi Bay (14,000 ng Sn/g) in Japan and Chennai port (11,871 ng Sn/g) in India were a little lower than our values in this study but in the same order of magnitude [9,12]. Except for some studies reporting tens (or hundreds) of ppb of TBT levels (Sado Estuary, Kaohsiung Harbor, and Gohyeon Bay) [22][23][24], the other regions in Table 2 showed TBT concentrations in the range of from 1137 to 5372 ng Sn/L [8,[24][25][26]. TBT concentrations in surface sediments from Gohyeon Bay in this study are higher than levels reported in other shipyard areas in Ulsan Bay (13,300 ng Sn/g) and Okpo Bay (11,700 ng Sn/g), South Korea in 1996, 7 years before the total ban of TBT [14].…”
Section: Comparison Of Butyltin Contamination With Other Studiescontrasting
confidence: 51%
“…Sediment TBT concentrations near a shipyard in Otuschi Bay (14,000 ng Sn/g) in Japan and Chennai port (11,871 ng Sn/g) in India were a little lower than our values in this study but in the same order of magnitude [9,12]. Except for some studies reporting tens (or hundreds) of ppb of TBT levels (Sado Estuary, Kaohsiung Harbor, and Gohyeon Bay) [22][23][24], the other regions in Table 2 showed TBT concentrations in the range of from 1137 to 5372 ng Sn/L [8,[24][25][26]. TBT concentrations in surface sediments from Gohyeon Bay in this study are higher than levels reported in other shipyard areas in Ulsan Bay (13,300 ng Sn/g) and Okpo Bay (11,700 ng Sn/g), South Korea in 1996, 7 years before the total ban of TBT [14].…”
Section: Comparison Of Butyltin Contamination With Other Studiescontrasting
confidence: 51%
“…In fact, G9 (1928 ng Sn g À1 ) presented the highest TBT value recently detected in South America. Other hotspots in the region, such as Bahía Blanca in Argentina (3228 ng Sn g À1 , (Delucchi et al, 2006)) and…”
Section: Butyltin (Bt) Levels In Sedimentsmentioning
confidence: 99%
“…In the Atlantic coast, Delucchi et al (2006) analyzed six surface sediments (Villarino Viejo, Puerto Cuatrenos, Maldonado, Puerto Galvan, Puerto Ingeniero, and Puerto Belgrano) at Blanca Bay estuary (Argentina) and found a wide range of TBT (ranging from <1.1 to 3,227 ng Sn g −1 dw) and DBT (ranging from <0.2 to 1,645 ng Sn g −1 dw) levels. Puerto Galvan presented the highest values of TBT in the inner zone of the estuary, which is the most active harbor in the area.…”
Section: Ots Contamination In Abiotic Matricesmentioning
confidence: 99%